Coronavirus disease 2019 and cardiovascular disease - Jenn-Yeu Song; Jian-You Huang; Yi-Chiung Hsu; Men-Tzung Lo; Chen Lin; Ta-Chung Shen; Min-Tser Liao; Kuo-Cheng Lu (Tzu Chi Medical Journal)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus behind the coronavirus disease 2019 (COVID-19) pandemic, is a type of RNA virus that is nonsegmented. Cardiovascular diseases (CVDs) increase the mortality risk of patients. In this review article, we overview the existing evidence regarding the potential mechanisms of myocardial damage in coronavirus disease 2019 (COVID-19) patients. Having a comprehensive knowledge of the cardiovascular damage caused by SARS-CoV-2 and its underlying mechanisms is essential for providing prompt and efficient treatment, ultimately leading to a reduction in mortality rates. Severe COVID-19 causes acute respiratory distress syndrome and shock in patients. In addition, awareness regarding COVID-19 cardiovascular manifestations has increased, including the adverse impact on prognosis with cardiovascular involvement. Angiotensin-converting enzyme 2 receptor may play a role in acute myocardial injury caused by SARS-CoV-2 infection. COVID-19 patients experiencing heart failure may have their condition exacerbated by various contributing factors and mechanisms. Increased oxygen demand, myocarditis, stress cardiomyopathy, elevated pulmonary pressures, and venous thrombosis are potential health issues. The combination of these factors may lead to COVID-19-related cardiogenic shock, resulting in acute systolic heart failure. Extracorporeal membrane oxygenation (ECMO) and left ventricular assist devices (LVADs) are treatment options when inotropic support fails for effective circulatory support. To ensure effective COVID-19-related cardiovascular disease (CVD) surveillance, it is crucial to closely monitor the future host adaptation, viral evolution, and transmissibility of SARS-CoV-2, given the virus's pandemic potential.